2017
DOI: 10.9770/jssi.2017.6.4(13)
|View full text |Cite
|
Sign up to set email alerts
|

Towards Sustainable Economic Development via Social Entrepreneurship

Abstract: This paper argues that social enterprises (SE) in EU Member States share at least following common features: the dominance of a social or societal objective over market goal, an apparent social responsibility, particularly in the field of profit distribution. However, numeric limits for the criteria of SE identification remain 'unclear': in the majority of cases there are no comprehensible requirements regarding the employment of vulnerable groups and the reinvestment of profits into social projects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…They respectively compared the meaning of the work itself and the firm-climate with financial aspects, particularly, the volume and stability of income and concluded that money has no primal importance, however Hosain and Hossain found job security has higher significance, but still it scored below job environment and atmosphere, which are again social, nonmonetary pillars. The same conclusions are equitable especially for the social enterprises which are often family owned: social atmosphere and job conditions can be more important reasons for activity and employment than profits and remuneration (Bilan, Mishchuk & Pylypchuk 2017). This field also requires more attention and careful generalization.…”
Section: Workplace Motivations and Expectations Of Benchmark Employees'mentioning
confidence: 82%
“…They respectively compared the meaning of the work itself and the firm-climate with financial aspects, particularly, the volume and stability of income and concluded that money has no primal importance, however Hosain and Hossain found job security has higher significance, but still it scored below job environment and atmosphere, which are again social, nonmonetary pillars. The same conclusions are equitable especially for the social enterprises which are often family owned: social atmosphere and job conditions can be more important reasons for activity and employment than profits and remuneration (Bilan, Mishchuk & Pylypchuk 2017). This field also requires more attention and careful generalization.…”
Section: Workplace Motivations and Expectations Of Benchmark Employees'mentioning
confidence: 82%
“…The role of corporations in societies is on a steep rise. Likewise, people's interest in CSR is increasing (Krajnakova et al, 2018), including the most advanced forms of its manifestation in social entrepreneurship (Bilan et al, 2017) and inter-institutional collaboration (Raišienė et al, 2019). Crane et al (2014) follow the mainstream in their theoretical reasoning and interpret the CSR as a disclosure that should be accompanied to various reports of corporations, governments, public sector organizations, non-government organizations and even international organizations.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The results have not confirmed this importance of employees in achieving the business goals of enterprises in SMEs. The concept of competitiveness must be associated with the concept of sustainable development (Bilan et al, 2017). In the context of sustainable development and competitiveness, Ahmedova (2015) highlights five key factors for sustainable development and competitiveness: access to finance, innovation activities, intellectual property-related activities, internationalization and implementation of best practices.…”
Section: Resultsmentioning
confidence: 99%